Traumatic brain injury related deaths in residents and non-residents of 30 European countries: a cross-sectional study - Sivco, Patrik; Plancikova, Dominika; Melichova, Juliana; Rusnak, Martin; Hereitova, Iva; Beranek, Vaclav; Cibulka, Roman; Majdan, Marek (Scientific reports, 2023)
The incidence and mortality of traumatic brain injuries (TBI) among non-residents to countries where they occur remains unknown, warranting epidemiological research. Epidemiological data are key to inform prevention and public health policies related to TBI, as well as to help promote safe travelling practice. The aim of this study was to analyse the epidemiological patterns of TBI-related deaths among residents and non-residents in 30 European countries in 2015 using standardised European level data on causes of death. A large-scale cross-sectional study analysing TBI-related deaths in 30 European countries in 2015 among residents and non-residents to the country of occurrence of the death was conducted. Data from death certificates collected on European level by Eurostat were used to calculate the numbers of TBI-related deaths and estimate crude and age-standardised mortality rates. Rates were stratified by country, sex, age-group and by resident status. External causes of the injury were determined using the provided ICD-10 codes. 40,087 TBI-related deaths were identified; overall about 3% occurred among non-residents with highest proportions in Turkey (11%), Luxembourg (9%) and Cyprus (5%). Taking into account tourism intensity in the countries, Bulgaria, Greece and Austria showed highest rates of TBI-related deaths in non-residents: 0.7,0.5 and 0.5 per million overnight stays, respectively. The pooled age-standardised TBI-related mortality in non-residents was 0.2 (95% CI 0.1-0.3), among residents 10.4 (95% CI 9.4-11.5) per 100,000. In non-residents, TBI-related deaths were shifted to younger populations (86% in < 35 years); in non-residents 78% were 15-64 years old. Falls were predominant among residents (47%), and traffic accidents among non-residents (36%). Male:female ratio was higher among non-residents (3.9), compared to residents (2.1). Extrapolating our findings, we estimate that annually 1022 TBI-related deaths would occur to non-residents in the EU-27 + UK and 1488 in Europe as a continent. We conclude, that the primary populations at risk of TBI-related deaths in European countries differ in several characteristics between residents and non-residents to the country of the occurrence of death, which warrants for different approaches in prevention and safety promotion. Our findings suggest that TBI occurring in European countries among non-residents present a problem worthy of attention from public health and travel medicine professionals and should be further studied.
Keywords: Young Adult; Řecko; Cross-Sectional Studies; Male; Kypr; Rakousko; mladý dospělý; Adolescent; Adult; Brain Injuries, Traumatic; dospělí; mužské pohlaví; mladiství; lidé; Greece; ženské pohlaví; Cyprus; Humans; průřezové studie; Austria; Female; lidé středního věku; Middle Aged; traumatické poranění mozku